Ground Prosopis juliflora Pods as Feed Ingredient in Poultry Diet: Effects on Growth and Carcass Characteristics of Broilers - Girma , Meseret; Urge, Mengistu; Animut, Getachew (International Journal of Poultry Science, 2011)
Three hundred and ninety six Hubbard Classic commercial day old chicks were used to determine the performance of broilers fed ration containing ground Prosopis juliflora pods (GPJP) at inclusion levels of 0 (T1), 10 (T2), 20 (T3) and 30% (T4) of the total ration. The experiment was arranged in a completely randomized design with four treatments and three replications with 33 birds per replicate. Birds were weighed in group every 7 days to determine Average Daily Gain (ADG). Feed offered and refusals were recorded every day and Feed Intake (FI) was calculated as the difference between the two. Data on ADG, FI and Feed Conversion Ratio (FCR) were analyzed for starter (1-21 days) and finisher (22-45 days) phases separately as well as for the entire experiment period (45 days). At the end of the experiment, four randomly selected birds from each replicate were slaughtered and dressed to determine carcass characteristics. Feed Intake (FI) during finisher phase [3386, 3340, 3336 and 3280 g (SEM = 29.54)] and the entire experiment period [4369, 4321, 4313 and 4248 (SEM = 27.41)], final live weight at the end of starter, finisher and the entire experiment period, ADG [40.8, 41.2, 39.9 and 36.4 (SEM = 1.41)] for T1, T2, T3 and T4, respectively and FCR for the entire experiment period were significantly lower (p